2022
DOI: 10.3892/mco.2022.2573
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary study of hypoxia markers in diffuse large B‑cell lymphoma

Abstract: While the association of hypoxia has been established in various types of solid cancers, little is known about its presence and existence in diffuse large B-cell lymphoma (DLBCL). The purpose of the present study was to evaluate the expression of hypoxia-inducible factor-1α (HIF-1α) and vascular endothelial growth factor A (VEGF-A) in DLBCL and to analyze the association of these factors with several clinical and pathological characteristics. The immunohistochemical protein expression of HIF-1α and VEGF-A was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, no studies have yet investigated the correlation between HIF-1α expression and serum VEGF levels in patients with DLBCL. In our previous preliminary research study, it was found that the expression of HIF-1α was positively correlated with the expression of VEGF in tissues 5 . The lower serum VEGF levels in the HIF-1α distribution greater than or equal to 40% group, compared to the HIF-1α distribution less than 40% group, may be due to the larger size of the lymphoma tumour being influenced by inflammation rather than angiogenesis 21 .…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…To the best of our knowledge, no studies have yet investigated the correlation between HIF-1α expression and serum VEGF levels in patients with DLBCL. In our previous preliminary research study, it was found that the expression of HIF-1α was positively correlated with the expression of VEGF in tissues 5 . The lower serum VEGF levels in the HIF-1α distribution greater than or equal to 40% group, compared to the HIF-1α distribution less than 40% group, may be due to the larger size of the lymphoma tumour being influenced by inflammation rather than angiogenesis 21 .…”
Section: Discussionmentioning
confidence: 89%
“…Secondly, the positive correlation between sIL-2R and VEGF, as well as between sIL-2R and tumour volume, suggests that the immune system may play a role in modulating tumour angiogenesis and growth in DLBCL. sIL-2R is a marker of T-cell activation and proliferation, and may reflect the distribution of immune infiltration and activation within the tumour microenvironment 5 , 18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation